Wound Healing Effects of Arnebia Densiflora Root Extracts on Rat Palatal Mucosa - Kosger, H. Huseyin; Ozturk, Mustafa; Sokmen, Atalay; Bulut, Eray; Ay, Sinan (European Journal of Dentistry, 2009)
Objectives: The aim of this study was to investigate wound healing effects of Arnebia densiflora (Nordm.) Ledeb. root extracts on rat palatal mucosa.Methods: A 10-mm full-thickness mucosal wounds were created on midline of rats’ palate by using scalpel. Inthe experimental groups, a ten percent extract of A. densiflora roots was topically applied once a day as ointment on the wounds. After wounding, tissue samples from palatal mucosa were harvested at 4, 7, 14 and 21 days and then evaluated histologically.Results: It was observed that 10% A. densiflora root extract has progressive effects on wound healing in experimental groups.Conclusions: This study suggests that A. densiflora root extract could be developed as a therapeutic agent for wound healing. (Eur J Dent 2009;3:96-99)
Keywords: Arnebia densiflora; Wound healing; Rat; Palatal mucosa